Kegiatan Praktek Pengawasan Pencegahan Dan Pelanggaran Pemilu 2024 - Antonio, Jason; Yani, Pitri; Hakim, Cristine Mulia; Tanuwijaya, Netanya Deecy; Calvin, Calvin; Tang, Jeffen; Christina, Christina; Fransisca, Violin; Joscelin, Joscelin; Irawan, Anthony; Yuliana, Yuliana; Drice, Eric; Stelyven, Stelyven; Lee, Jenny; Centrico, Centrico; Leo, Leo; Sakana, Fayat; Nicholas, Nicholas (Universitas Pahlawan Tuanku Tambusai, 2024)
Election monitoring is a crucial aspect of ensuring the integrity and fairness of the electoral process. This article discusses the implementation of election monitoring methods for the 2024 elections with a focus on technology and community participation. Methods used include technology-based monitoring, volunteer training, and cooperation between monitoring agencies and the community. Findings indicate that the application of technology and direct community involvement can enhance transparency and accountability in elections. The study provides recommendations for strengthening monitoring systems in future elections. Keywords: Election Monitoring, Technology, Community Participation, Transparency, Accountability